Over the horizon: Exploring the conditions of a post-growth world. (April 2019) - Crownshaw, Timothy; Morgan, Caitlin; Adams, Alison; Sers, Martin; Britto dos Santos, Natália; Damiano, Alice; Gilbert, Laura; Yahya Haage, Gabriel; Horen Greenford, Daniel
Maintaining steady growth remains the central goal of economic policy in most nations. However, as evidenced by the advent of the Anthropocene, the global economy has expanded to a point where limits to growth are appearing. Facing the end of growth requires a careful re-examination of plausible future conditions. We draw on a diverse literature to present an interdisciplinary exploration of post-growth conditions in the areas of climate change, ecological impacts, governance, and education, finding that such conditions may invalidate many prevalent assumptions regarding the future. The post-growth world, while subject to significant uncertainty and heterogeneity, will be characterized by profound hazards and discontinuities for both human and natural systems. Furthermore, we argue that an economic paradigm change will be predicated on an involuntary and unplanned cessation of growth. This implies a necessary strategic expansion of the heterodox economic discourse to formulate appropriate responses in view of likely post-growth realities.